Protein cages as building blocks for superstructures. Issue 2 (16th June 2021) - Sun, Ruoxuan; Lim, Sierin
Abstract: Proteins naturally self‐assemble to function. Protein cages result from the self‐assembly of multiple protein subunits that interact to form hollow symmetrical structures with functions that range from cargo storage to catalysis. Driven by self‐assembly, building elegant higher‐order superstructures with protein cages as building blocks has been an increasingly attractive field in recent years. It presents an engineering challenge not only at the molecular level but also at the supramolecular level. The higher‐order constructs are proposed to provide access to diverse functional materials. Focussing on design strategy as a perspective, current work on protein cage supramolecular self‐assembly are reviewed from three principles that are electrostatic, metal‐ligand coordination and inherent symmetry. The review also summarises possible applications of the superstructure architecture built using modified protein cages.